Jurisdiction in Digital Copyright Lawsuit - Unggul Prayudho Satriyo (Universitas Muhammadiyah Tangerang, 2024)
The copyright is one of form in intellectual property rights. It comprises of work being protected in multiple forms. With the advancement of modern world, the copyright have move it protection, from mere reproduction right for work in book, as an authorship, to the modern form in the digital world. The move into the digital form of work in copyright have open the possibilities of more effective distribution or right, including its distribution. The easiness of the distribution in digital format, made it hasle free, and work of copyright may be enjoyable in multiple location at once. This then lead to the dispute resolution that is currently available for the copyright cases in civil lawsuit. The available avenue for copyright dispute is heavily rest on the commercial court that have been designated court that have the absolute jurisdiction in civil litigation of the copyright. Nature of the digital copyright have made it solution to the dispute resolution to bel clear and concise. Through this research, by employing doctrinal method, solution for the avenue jurisdiction over dispute in copyright will be clear.